Estimating Historical CGIAR Research Investments - Elven, S.; Krishnan, L. (CGIAR Independent Science and Partnership Council, 2018)
CGIAR donors as well as other stakeholders have recognized the importance of credible evidence on the outputs and outcomes associated with CGIAR research, particularly at system level (System Council, 2016). The importance of tracking the research areas towards which investments are directed is less acknowledged, yet this information is essential for prioritizing impact assessments and conducting cost benefit analyses at the system level. Additionally, donors have sought strategic guidance in the past, from advisory bodies such as the ISPC, on how best to prioritize CGIAR investments within the overall research agenda. Such system level approaches require an understanding of current research invest-ment allocations.